STUDENTS’ ABILITY IN USING PAIRED CONJUNCTION IN SIMPLE SENTENCE - Marini Marini; Melda Yeni; Samsul Amri (Program Studi Pendidikan Bahasa Inggris, 2020)
The goal of this research is to know the students' ability in using paired conjunction in a simple sentence. Based on the limitation of the problem, the researchers limit the problem in using paired conjunction just focuses on the use of not only ..... but also, both ..... and, either ..... or, and neither ..... nor. Before doing the research, the researchers observed to know the number of classes in the eighth grade of SMP PGRI Tembilahan. The number of eighth-grade students just consists of one class, namely Class A. The population of this research was all of the eighth-grade students because the sample of population less than 100 the researcher used total sampling technique. The researchers used a quantitative method to get the data needed. The research instrument is tested and collected by students’ test scores where they were asked to identify the paired conjunction in a simple sentence with the total correct paired conjunction (30). So that, each correct paired conjunction was scored by 3.3. Based on the result of the test, the mean score of their ability in using paired conjunction is 70.62. It is categorized good level, which includes in the interval 61-80. Where there are no students who got in a very good score, five students obtained a good score and there is no gained in enough, poor, and very poor score. So, based on that explanation, it can be concluded that their ability in using paired conjunction in the simple sentence at eighth grade of SMP PGRI Tembilahan include in the average was enough and understanding to use paired conjunction.